The Pink Wave across Parliaments: What Factors Explain the Percentage of Women in National Politics? - Viana, Sabrina C. (My University, 2020)
This quantitative research paper examines the factors that explain the percentage of women in national parliament. The seven independent variables used in this study are freedom scores, literacy rates, democracy levels, corruption perception index, gender quotas, population density and gross domestic product (GDP per capita). The dependent variable is the percentage of women in national parliaments. To analyze the relationship between the independent variables and dependent variable, a correlation analysis, four scatterplots and an analysis of variation (ANOVA) were generated. The correlation analysis revealed that five out of seven independent variables were statistically significant: freedom scores, literacy rates, democracy levels, corruption perception index, and gender quotas. Ultimately, gender quotas proved to be the most statistically significant out of the five showcasing the influence and positive feedback that this variable, if implemented, would have on the percentage of women in parliament.